Epipolar Geometry‐Based Visual Servoing of Soft Endoscopic Manipulator for Transoral Laser Ablation. (13th November 2022) - Fang, Ge; Wang, Xiaomei; Ho, Justin D. L.; Wang, Kui; Chow, Chun-Kit; Lee, Kit-Hang; Xie, Xiaochen; Tang, Wai Lun; Liang, Liyuan; Chang, Hing-Chiu; Juan, Chun-Jung; Liu, Yun-hui; et al.
Abstract : Soft manipulators integrated with optical laser fibers offer new opportunities for endoscopic noncontact laser surgery. To achieve precise laser projection in a confined workspace and avoid damage, a controller with high accuracy and stability is required. An effective way is to close the control loop. Therefore, a visual servo controller that allows automatic laser spot steering using soft manipulators is proposed. An epipolar geometry model is established to acquire the inverse transition mapping from image to actuation. With this mapping, a feedback controller is derived without prior information of tissue surface geometry. Experimental validation demonstrates accurate path following using a magnetic resonance‐safe manipulator, with root‐mean‐square (RMS) tracking errors <4 pixels (140 μm) in the camera view. This is maintained even throughout 70 repeated cycles, with a maximum tracking error <11.32 pixels (≈396.2 μm). The controller enables laser spot following of the mouse cursor with an RMS tracking error of 3.97 pixels (≈180.5 μm). Ex vivo tissue ablation tests are conducted to validate the laser ablation pattern, with an RMS tracking error of about 5.75 pixels (≈201.3 μm). A laser ablation test is conducted under magnetic resonance imaging (MRI) to validate the feasibility of MRI‐guided laser surgery. Abstract : A visual servoing controller is proposed, allowing automatic laser spot steering for endoscopic noncontact laser microsurgery using soft manipulators. An epipolar geometry model is established to acquire the transition mapping from image to actuation, with which a feedback controller is derived without prior information of tissue surface geometry. Experimental validation demonstrates accurate path following using a magnetic resonance‐safe manipulator.